2017
DOI: 10.1002/2016jc012413
|View full text |Cite
|
Sign up to set email alerts
|

Small‐scale open ocean currents have large effects on wind wave heights

Abstract: Tidal currents and large‐scale oceanic currents are known to modify ocean wave properties, causing extreme sea states that are a hazard to navigation. Recent advances in the understanding and modeling capability of open ocean currents have revealed the ubiquitous presence of eddies, fronts, and filaments at scales 10–100 km. Based on realistic numerical models, we show that these structures can be the main source of variability in significant wave heights at scales less than 200 km, including important variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

26
163
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 156 publications
(190 citation statements)
references
References 65 publications
26
163
1
Order By: Relevance
“…Indeed, currents impact the dispersion of surface waves, and surface current fluctuations can lead to the formation of anomalous large-amplitude waves. Joint analysis of numerical modeling outputs and satellite measurements have confirmed that spatial wave height variations result from these refraction effects (Ardhuin et al, 2017;Kudryavtsev et al, 2017;Quilfen et al, 2018). Ultimately, these impacts can lead to significant ray deflection (Dysthe, 2001;Gallet & Young, 2014;Kenyon, 1971;White & Fornberg, 1998).…”
Section: Introductionmentioning
confidence: 88%
“…Indeed, currents impact the dispersion of surface waves, and surface current fluctuations can lead to the formation of anomalous large-amplitude waves. Joint analysis of numerical modeling outputs and satellite measurements have confirmed that spatial wave height variations result from these refraction effects (Ardhuin et al, 2017;Kudryavtsev et al, 2017;Quilfen et al, 2018). Ultimately, these impacts can lead to significant ray deflection (Dysthe, 2001;Gallet & Young, 2014;Kenyon, 1971;White & Fornberg, 1998).…”
Section: Introductionmentioning
confidence: 88%
“…In practice we use the locations (x , y ) that have the right azmuth θ , and that are closest to (x, y), separated by a distance r(θ ). The variations of U S,1D (θ ) over the distance r(θ ), which is typically 25 less than 50 km, is mostly due to the effect of currents on waves (Ardhuin et al, 2017b).…”
mentioning
confidence: 99%
“…These will be discussed in other 25 publications. We only point out here that the sea state variability at small scales is probably dominated by the effect of ocean currents (Ardhuin et al, 2017b). It is thus logical to measure waves and currents together, and possibly further use the measured variability of sea state parameters to further constrain the magnitude of current gradients.…”
mentioning
confidence: 99%
See 2 more Smart Citations